2016
DOI: 10.1002/hbm.23178
|View full text |Cite
|
Sign up to set email alerts
|

Aging modulates the oscillatory dynamics underlying successful working memory encoding and maintenance

Abstract: Working memory is central to the execution of many daily functions and is typically divided into three phases: encoding, maintenance, and retrieval. While working memory performance has been repeatedly shown to decline with age, less is known regarding the underlying neural processes. We examined age-related differences in the neural dynamics that serve working memory by recording high-density magnetoencephalography (MEG) in younger and older adults while they performed a modified, high-load Sternberg working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 73 publications
9
93
2
Order By: Relevance
“…For example, Proskovec and colleagues reported widespread neural activity in left fronto-temporal regions of both young and older adults during the encoding and maintenance periods of a verbal working memory task, but only older adults also engaged the right prefrontal cortices during task performance. 156 Results for the retrieval phase of working memory were reported by Aine et al 157 Notably, no age-related differences in working memory performance were observed in either of these studies. 156-157 Together, these studies support the compensation hypothesis of cognitive aging.…”
Section: Healthy Agingmentioning
confidence: 61%
See 3 more Smart Citations
“…For example, Proskovec and colleagues reported widespread neural activity in left fronto-temporal regions of both young and older adults during the encoding and maintenance periods of a verbal working memory task, but only older adults also engaged the right prefrontal cortices during task performance. 156 Results for the retrieval phase of working memory were reported by Aine et al 157 Notably, no age-related differences in working memory performance were observed in either of these studies. 156-157 Together, these studies support the compensation hypothesis of cognitive aging.…”
Section: Healthy Agingmentioning
confidence: 61%
“…156 Results for the retrieval phase of working memory were reported by Aine et al 157 Notably, no age-related differences in working memory performance were observed in either of these studies. 156-157 Together, these studies support the compensation hypothesis of cognitive aging. 136 Essentially, older adults recruited more neural resources during working memory performance across encoding, maintenance, and retrieval periods compared with younger adults, while performance was relatively equal between groups.…”
Section: Healthy Agingmentioning
confidence: 61%
See 2 more Smart Citations
“…The MEG preprocessing and imaging analysis pipeline was closely based on the methods reported in our recent WM papers (Heinrichs-Graham & Wilson, 2015; McDermott et al, 2015; Proskovec, Heinrichs-Graham, & Wilson, 2016; Wiesman et al, 2016). The continuous magnetic time series was divided into epochs of 6,900 ms duration, with 0 ms being the onset of the encoding grid and the baseline being the −400–0 ms time bin (see Fig.…”
Section: Methodsmentioning
confidence: 99%